Etika Pemerintahan dalam Optimalisasi Regulasi Laporan Harta Kekayaan Penyelenggara Negara - Sholihah, Shofi Siti; Qothrunnada, Qothrunnada; Oktaviani, Frida Nur; Akbar, Idil (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2023)
LHKPN is one form of realization of ideal government ethics. It’s because government ethics sees that in state administration, regulation is needed so that the duties and functions of the service can be fulfilled. However, the level of compliance with wealth reporting has only reached the level of transparency and does not yet indicate the validity of the report. Apart from that, regulations that are less strict in providing administrative sanctions to violators are something that needs attention. This research uses a qualitative descriptive research methode, aims to find out how the ideal conditions compare with the reality of reporting state administrators' assets and to find out what the government must do so that the LHKPN can be implemented well. Apart from the implementation of LHKPN which is not running well, this research explains several things that the government must do to improve state administrators who comply with LHKPN.